CO2 laser promoted oxygen vacancy-active oxygen cycle in DRM on Ni/CeO2. (15th June 2023) - Liu, Hongchuan; Dong, Meirong; Xiong, Junchang; Yang, Junshu; Ning, Jingyun; Liang, Youcai; Lu, Jidong
Graphical abstract: Highlights: DRM was driven by a mid-infrared CO2 laser at mild catalyst layer temperatures. Better low-temp reactivity obtained under laser treatment than in thermocatalysis. CO2 laser generated more active sites and oxygen vacancies in catalyst system. CO2 laser enhanced the key oxygen vacancy-active oxygen cycle in DRM. Abstract: The global climate change has led to great interest in dry reforming of methane (DRM) to produce syngas from two greenhouse gases, CO2 and CH4 . In order to investigate the reaction characteristics and mechanism under mid-infrared light irradiation, a 10.6 µm CO2 laser was introduced as an energy source to perform the complete DRM process on Ni/CeO2 at mild temperature. This scheme was compared with the traditional thermal mode under similar catalyst layer temperature. The laser-driven mode yielded significantly better performance around the DRM light-off temperature of the catalytic system, due to several-fold higher reactant conversion and product selectivity than in thermocatalytic mode. Based on a series of characterizations, the CO2 laser not only generated more than twice the number of oxygen vacancies than that in thermal mode at pre-reduction stage, but also enhanced the dissociative adsorption of CO2 and the circulation of oxygen vacancy-reactive oxygen at methane reforming stage. This study provides insight into the mechanism of CeO2 materials for DRM under mid-infrared illumination.